Políticas públicas em cidadania fiscal: análise do comportamento do cidadão usuário do Programa Todos com a Nota, do Governo do Estado de Pernambuco - Silva, Robson Martins de Abreu (2012)
The main goal of this research was to verify if the campaign 'Todos com a Nota – Módulo Esportivo', instituted by the Government of the State of Pernambuco, provides awareness to the citizen about the social importance of always asking for the tax invoice when paying for goods and services that are subject to the incidence of the ICMS, as well as infer which is the aware population proportion . The theoretical reference embraced knowledge from several fields related to the sphere of the necessity of fiscal awareness, such as tax obedience; tax compliance; tax evasion; tax administration; taxpayer and consumer behavior; fiscal education and fiscal citizenship. In order to reach the goal, it was performed a consumer behavior research at the attending centres for the users of the campaign. The chosen method was a structured survey. The results suggest that the campaign 'Todos com a Nota' provides awareness, and the proportion of the citizens that become aware stays between 5.34% and 10.66% of the users population of 'Modulo Esportivo', that employs magnetic cards to trade receipts for tickets for watching games from the brazilian and state championships of professional soccer. Although this proportion might seem small, deserving a bigger attention from the public administration, if compared to the proportion of citizens that already entered the campaign aware, the improvement was about, at least, 7.21 times, with 95% trust.